Adoption Intention and Factors Influencing the Use of Gerontechnology in Chinese Community-Dwelling Older Adults: A Mixed-Methods Study - Huang, Huanhuan; Chen, Zhiyu; Cao, Songmei; Xiao, Mingzhao; Xie, Liling; Zhao, Qinghua (Frontiers in Public Health, 2021)
Objectives: To explore the Chinese community-dwelling older adults’ intention and influencing factors to adopt gerontechnology. Design: A mixed-methods sequential explanatory design with an inductive approach was employed. In Phase 1, a self-made questionnaire, multi-factor logistic regression was used to analyze the adoption Intention and factors influencing the use of gerontechnology from August 2018 to December 2019. In phase 2, participants were recruited and completed a semi-structured interview to explore and expand the influence factors from May 2020 to July 2020. Settings: 12 communities in three districts of Chongqing, China. Participants: Community-dwelling older adults were included. Results: A total of 1180 older adults completed quantitative study, two-thirds participants (68.7%) showed adoption intention and identified 8 influential factors. 19 participants completed qualitative study and 4 themes were explored. Through a summarized understanding of the qualitative and quantitative data, a conceptual model of influential factors including predicting factors, enabling factors, and need factors was constructed. Conclusions: This study reveals that most Chinese community-dwelling older adults welcome the emergence of new technologies. However, there are still many complex and systematic factors hindering further using, which extends previous technology, acceptance models, and theories, and contributes to the existing resource base.